Dilemmas of intervention : social science for stabilization and reconstruction - Davis, Paul K., 1943- (Rand Corporation monograph series., 2011)
Governments intervening in post-conflict states find themselves beset with numerous challenges and profound dilemmas: it is often unclear how best to proceed because measures that may improve conditions in one respect may undermine them in another. This volume reviews and integrates the scholarly social-science literature relevant to stabilization and reconstruction (S & R), with the goal of informing strategic planning at the whole-of-government level. The authors assert that S & R success depends on success in each of four component domains -- political, social, security, and economic. The authors discuss each domain separately but emphasize their interactions and the idea that the failure of any component can doom S & R as a whole. The authors also focus on a number of dilemmas that intervenors in post-conflict states face -- such as between short- and long-term goals and whether to work through or around the state's central government -- and suggest how these dilemmas can be confronted depending on context.